MODERN OPPORTUNITIES FOR INCREASING THE EFFICIENCY OF HIV INFECTION PROPHYLAXIS (LITERATURE REVIEW) - Kalniyazova Inobatxon Bayramovna; Yoldoshova Nilufar Xudargan qizi; Kirgizboyeva Xonzoda Abulqosim qizi (Western European Studies, 2026)
In the article, the author reviews domestic and foreign literature on the epidemiology and prevention of HIV infection among serodiscordant couples. This article presents scientifically based explanations of the epidemiological characteristics of HIV infection in serodiscordant couples and the development of the epidemic process, as well as social risk factors from an epidemiological point of view. Detailed information on the effectiveness of antiretroviral treatment and disease prevention is provided.The proportion of women among new cases of infection in our country is increasing day by day, and the feminization of the HIV/AIDS epidemic among older women compared to women of reproductive age requires the strengthening of preventive programs and measures aimed at preventing the spread of infection.
Keywords: HIV infection; serodiscordant couples; epidemic process